Ghrelin action on GnRH neurons and pituitary gonadotropes might be mediated by GnIH-GPR147 system - Celik, Onder; Celik, Nilufer; Aydin, Suleyman; Aygun, Banu Kumbak; Haberal, Esra Tustas; Kuloglu, Tuncay; Celik, Sudenaz (Walter de Gruyter Gmbh, 2016)
Acylated ghrelin (AG) effect on GnRH secretion is mediated, at least in part, by GH secreta-gogue receptor (GHS-R) which is present in the GnRH neurons. As the acylation is mandatory for binding to GHS-R, unacylated isoform of ghrelin (UAG) action on gonadotropin secretion is likely to be mediated by other receptors or mediators that have not been identified yet. UAG, therefore, may act partially via a GHS-R-independent mechanism and inhibitory impact of UAG on GnRH neurons may be executed via modulation of other neuronal networks. Ghrelin and gonadotropin inhibitory hormone (GnIH), two agonistic peptides, have been known as important regulators of reproductive events. Potential impact of ghrelin on the activity of GnIH neurons is not exactly known. Both GnIH and ghrelin are potent stimulators of food intake and inhibitors of gonadotropin release. By binding G-protein coupled GnIH receptor (GnIH-R), GPR147, which is located in the human gonadotropes and GnRh neurons, GnIH exerts an inhibitory effect on both GnRH neurons and the gonadotropes. The GnIH-GPR147 system receives information regarding the status of energy reservoir of body from circulating peptides and then transfers them to the kisspeptin-GnIH-GnRH network. Due to wide distribution of this network in brain GnIH neurons may project on ghrelin neurons in the arcuate nucleus and contribute to the regulation of UAG's central effects or vice versa. Together, the unidentified ghrelin receptor in the hypothalamus and hypophysis may be GnIH-R. Therefore, it is reasonable that ghrelin may act on both hypothalamus and hypophysis via GnIH-GPR147 system to block gonadotropin synthesis and secretion.
Keywords: ghrelin; GnIH-GPR147 system; GnRH neurons; pituitary gonadotropes